Juridical Implications of The Sustainable Finance Principles Implementation in the Banking Sector on the Obligations of Sustainable Reporting - Abubakar, Lastuti; Handayani, Tri (Jurnal Dinamika Hukum, 2019)
OJK has issued regulation No.51/POJK.03/2017 on The Application of Sustainable Finance for Financial Services Institution, Issuer and Public Companies, requires all financial services institutions, including banks to applied sustainable financial principles. While some of the principles of sustainable finance are already part of banking regulation such the obligation to implement risk management and governance, they have not specifically accommodated the demand to integrate economic, social and environmental aspect as a pillar of sustainable banking. This study is used normative juridical approaches and analytical descriptive research specifications, legal issues are how to implement sustainable financial principles in the banking sector and urgency of the bankâ€™s sustainable report as an effort to identify bank compliance with sustainable financial principles. Banks are required to make and publish sustainable financial statements as a form of bank accountability to all stakeholders to comply with governance principles, in particular transparency obligations.Â This sustainable reporting is a form of report conducted by a company in order to disclose or communicate to all stakeholders on good environmental, social and governance performance in an accountable manner.Â